Osteogenesis imperfecta and bisphosphonate - Panji Sananta; Alva Pribadi (Jurnal Kedokteran Syiah Kuala, 2022)
Osteogenesis Imperfecta (OI) is defined as genetic disorders presented by various clinical presentations, such as bone deformities, abnormalities in dental structure, deafness, blue sclera, growth retardation, and ligament laxity. Most OI patients have a mutation in collagen type I alpha chains genes, COL1A1 and COL1A2. All those genes are expressed in osteoblasts and mostly responsible for the direct metabolism of collagen type I. Bisphosphonates (BPs), as potent antiresorptive agents, inhibit bone resorption through direct actions in the osteoclasts. They cut the excessive turnover rate and prevent bone tissue loss. The selection of BP regimens for OI patients is still a significant obstacle due to the lack of standardization of therapy and the lack of published evidence to determine the most appropriate type for different OI patients. The current use of BP and its benefit in OI are discussed in this review.